2021
DOI: 10.3389/fcell.2021.643996
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TFE3 Protects Against Lysosomal Malfunction-Induced Pyroptosis in Random Skin Flaps via ROS Elimination

Abstract: Increasing evidence indicates that pyroptosis, a new type of programmed cell death, may participate in random flap necrosis and play an important role. ROS-induced lysosome malfunction is an important inducement of pyroptosis. Transcription factor E3 (TFE3) exerts a decisive effect in oxidative metabolism and lysosomal homeostasis. We explored the effect of pyroptosis in random flap necrosis and discussed the effect of TFE3 in modulating pyroptosis. Histological analysis via hematoxylin-eosin staining, immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…Therefore, whether these kinases will be included in the therapy effect of BA needs further study. Third, in term of the theory of flap survival (Wu et al, 2019), the greater the chance of necrosis of the distal flap, the control group in this experimental model had complete necrosis in the Area III and a small part of survival in the Area II, which was consistent with the previous study (Li et al, 2021; Lin et al, 2018). Though BA treatment significantly improved the survival rate in Area II, it would be better to have a positive control group in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, whether these kinases will be included in the therapy effect of BA needs further study. Third, in term of the theory of flap survival (Wu et al, 2019), the greater the chance of necrosis of the distal flap, the control group in this experimental model had complete necrosis in the Area III and a small part of survival in the Area II, which was consistent with the previous study (Li et al, 2021; Lin et al, 2018). Though BA treatment significantly improved the survival rate in Area II, it would be better to have a positive control group in this study.…”
Section: Discussionsupporting
confidence: 89%
“…When the flap size is too large or the flap's width‐to‐length ratio exceeds 1:2, narcosis develops in the distal portion of the flap (El Shaer et al, 2019). Therefore, a lot of studies have engaged to improve the survival of the skin flap including delayed surgery (Byun et al, 2020), biomaterial (Mao et al, 2019), and even gene intervention (Li et al, 2021). Despite these significant advancements, the therapeutic necessity to be able to harvest bigger portions of skin flaps remains unmet.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA Neat1 is associated with NLRP3 , NLRC4 , and AIM2 inflammasomes in mouse macrophages to increase their assembly and subsequent pro-caspase-1 processing ( Zhang et al, 2019 ). ROS-induced lysosome malfunction is a vital inducement of pyroptosis, and the arginine metabolism pathway participates in NLRP3 inflammasome inhibition ( Jiang et al, 2021 ; Li et al, 2021 ). Glycolytic metabolism can impose stress on DNA replication and activate AIM2 inflammasome ( Fidler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the accumulation of ROS results in neutrophil infiltration, increased protease release, and the formation of several oxidative intermediates (Sies & Jones, 2020). Excessive ROS generation causes partial or complete necrosis of the flap (Li et al, 2021). The first-line defense against accumulated superoxide anion radicals is SODs, while GSH-Px is upregulated to eliminate peroxides and hydroxyl radicals, and PB2's antioxidant effects were investigated using these enzymes (Taysi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%